The social and economic origins of monarchy in Jordan - Tell, Tariq (Middle East today, 2013)
An interpretative history of the emergence and consolidation of the modern state in Jordan, this book examines the resilience of the Hashemite monarchy and the economic sources of social power under Ottoman, British, and post-colonial Hashemite rule.